Biomedical Waste Management in Public Health Centers in Lome, Togo (African Journal of Biomedical Research, 2022)
This study aims to contribute on improving the solid biomedical waste management in public health facilities in the municipality of Gulf 4 of Grand Lomé, by a descriptive method based on surveys and observations. 42.25% of the staff members were trained in biomedical waste management. Waste sorting was not effective in all units: 55.56% have already had at least one accident. These observations can be used to define a new strategy that will improve the management of solid biomedical waste in health facilities.
Keywords: Keywords: Biomedical waste, biomedical waste management, sorting, accident.